Altering fatty acid availability does not impair prolonged, continuous running to fatigue: evidence for carbohydrate dependence - Leckey, J. J.; Burke, L. M.; Morton, J. P.; Hawley, J. A. (Journal of Applied Physiology, 2016)
We determined the effect of suppressing lipolysis via administration of nicotinic acid (NA) on fuel substrate selection and half-marathon running capacity. In a single-blinded, Latin square design, 12 competitive runners completed four trials involving treadmill running until volitional fatigue at a pace based on 95% of personal best half-marathon time. Trials were completed in a fed or overnight fasted state: 1) carbohydrate (CHO) ingestion before (2 g CHO/kg·body mass) and during (44 g/h) [CFED]; 2) CFED plus NA ingestion [CFED-NA]; 3) fasted with placebo ingestion during [FAST]; and 4) FAST plus NA ingestion [FAST-NA]. There was no difference in running distance (CFED, 21.53 ± 1.07; CFED-NA, 21.29 ± 1.69; FAST, 20.60 ± 2.09; FAST-NA, 20.11 ± 1.71 km) or time to fatigue between the four trials. Concentrations of plasma free fatty acids (FFA) and glycerol were suppressed following NA ingestion irrespective of preexercise nutritional intake but were higher throughout exercise in FAST compared with all other trials (P < 0.05). Rates of whole-body CHO oxidation were unaffected by NA ingestion in the CFED and FAST trials, but were lower in the FAST trial compared with the CFED-NA trial (P < 0.05). CHO was the primary substrate for exercise in all conditions, contributing 83-91% to total energy expenditure with only a small contribution from fat-based fuels. Blunting the exercise-induced increase in FFA via NA ingestion did not impair intense running capacity lasting ~85 min, nor did it alter patterns of substrate oxidation in competitive athletes. Although there was a small but obligatory use of fat-based fuels, the oxidation of CHO-based fuels predominates during half-marathon running.